1994
DOI: 10.1099/00221287-140-4-839
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression by the HlyX protein of Actinobacillus pleuropneumoniae

Abstract: The hlyX gene of the swine pathogen Actinobacillus pleuropneumoniae and the fnr gene of Escherichia coli encode very similar proteins. The hlyX gene is able to complement Afnr mutations and will permit the growth of E. coli fnr strains in nitrate minimal salts medium under anoxic conditions. In addition, the hlyX gene product appears to induce the expression of a latent haemolytic activity as evidenced by the presence of a strong zone of haemolysis around E. coli (hlyX+) colonies grown on bovine or ovine blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The suggested influence of other factors coregulating the expression of HlyX-dependent genes is supported by the work of Soltes and MacInnes (42), who showed that HlyX-dependent expression of a frdA-lacZ fusion in E. coli varied depending on growth phase and carbon source. Therefore, we hypothesize that as-yet-unknown factors in BALF are responsible for upregulation of aspartase activity and transcription of aspA.…”
Section: Discussionmentioning
confidence: 49%
“…The suggested influence of other factors coregulating the expression of HlyX-dependent genes is supported by the work of Soltes and MacInnes (42), who showed that HlyX-dependent expression of a frdA-lacZ fusion in E. coli varied depending on growth phase and carbon source. Therefore, we hypothesize that as-yet-unknown factors in BALF are responsible for upregulation of aspartase activity and transcription of aspA.…”
Section: Discussionmentioning
confidence: 49%
“…All of these factors may contribute to the virulence of this bacterium. A. pleuropneumoniae also responds to ironrestricted conditions by inducing the synthesis of a specific subset of outer-membrane proteins (OMPs) (Deneer & Potter, 1989 ;Niven et al, 1989 ;Soltes & MacInnes, 1994 ; M. Archambault, personal communication), including two membrane-bound transferrinspecific receptors called TbpA and TbpB (Gerlach et al, 1992a, b ;Gonzalez et al, 1995). Although it was tempting to speculate that one of these proteins might serve as a receptor for a siderophore, preliminary bioassays by Deneer & Potter (1989) did not demonstrate any siderophore production in A. pleuropneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…An A. pleuropneumoniae FNR homologue, HlyX, has been found to induce hemolytic activity in E. coli under anoxic conditions and to be able to complement E. coli fnr deletions (18,26). Like FNR, HlyX contains four iron-sulfur clusters responsible for the DNA-binding ability of the protein (12).…”
mentioning
confidence: 99%